(untitled) (Journal of Geography and Environmental Management, 2016)
In article climatic fl uctuations of the annual sums of deposits and a river drain on an example of Ishimsky water economic pool are considered at various forms of atmospheric circulation on classifi cation G.Ja. Vangengejma’s W, C and Е.